Standardization of genetic transformation protocols in Escherichia coli and Agrobacterium tumefaciens for the generation of a collection of gene constructs (2018)
An important tool in plant genetic engineering is the vectors or genic constructs that contain reporter genes, utilized to facilitate the standardization of genetic transformation protocols. The objective of this study was evaluate genetic transformation protocols for generate in a quick and confinable manner, a base collection of genic constructs in Escherichia coli strain DHα and Agrobacterium tumefaciens strains LBA 4404, EHA 105 y C58, using 25 binary vectors (pSK1019, pMP2482 y 23 de la serie pCAMBIA) that contain the reporter genes gfp and gus, by using the heat shock and electroporation techniques. The transformants confirmation was made by PCR amplification and by restriction enzymes assay with Eco RI and Xho I. These approaches allowed verifying the presence Successful of the 25 vectors inside the used bacteria. The results indicate that it is necessary to standardize the transformation protocols in the bacterial strains to be used because they do not all transform with the same conditions and this work can be a reference for the standardization in other laboratories of genetic transformation when working in a massive way.